(untitled) (Journal of Student Affairs in Africa, 2021)
The number of students enrolled in higher education outside their countries of origin increased from 0.8 million in 1975, to 2.1 million in 2000, and to 3.7 million in 2009 (Ryan, 2012). This growing trend of student mobility leads to increased university competition for students around the globe. However, little is known about the experiences of international students in Africa. This lack of understanding could leave the continent at a disadvantage for attracting and retaining international students, while other parts of the world continue to benefit. To begin to address this gap, I conducted a qualitative phenomenological study at one private university in East Africa that attracts about 20% of its population as international students. As International Student Coordinator at this university, I interviewed 13 graduate students from various countries and conducted participant observations on campus for three years. I aimed to understand students’ perceptions of their learning experiences. This article focuses on students’ non-academic learning. Students’ positive and negative experiences highlighted the difference that student affairs and administrative staff can make in the quality of students’ educational experiences. A needs model shed light on students’ non-academic experiences. Student affairs and administrative staff were essential in 1) providing pre-arrival information, 2) meeting students’ initial basic needs, 3) connecting them with others, keeping immigration documents current, and 5) understanding the new academic system. Ecologically, students were required to make a variety of connections in their adjustment process on campus and beyond.If the university could adequately address international students’ non-academic issues, then students would be better able to focus on their main purpose: their academics. It is recommended that the university revisit its procedures and develop more holistic international-student-friendly policies. Then, it could better support the learning of its present students and attract more international students, thereby more greatly impacting the world.